CONFLICT OF IMPERSONAL AND PERSONAL SOURCE OF SOCIAL LIFE IN THE ERA OF MODERNISM AND POSTMODERNISM - Сабадуха, В. О. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the article investigated the epoch of modernism and postmodernism on the basis of conception of four levels of essential powers of person. Proved that the anthropological content of these eras is the conflict personal and impersonal manifestations of social life.